Shedding light on indoor tanning - Manne, Sharon L.; Heckman, Carolyn J. (Springer Netherlands, 2012)
Since the industrialization and urbanization of the Western workforce, tanned skin has been perceived increasingly as attractive and fashionable for naturally light-skinned individuals. However, in addition to causing tanning, photo-aging, and other health effects, ultraviolet radiation (UV) is a well-known carcinogen. Despite wide-spread awareness of UV risks, tanning has become increasingly popular in several Western countries including the USA. While millions of individuals tan indoors each day, relatively little is known about this phenomenon. This book fills that gap by providing an overview of indoor tanning, reasons for its popularity, its risks including skin cancers, and the public health context surrounding the behavior. We have invited some of the preeminent experts in the field to summarize the existing scientific literature for each of the chapters. Shedding Light on Indoor Tanning is an up-to-date and comprehensive book that provides a unique and essential overview of the most significant current issues related to indoor tanning for scientists, educators, students, clinicians, and the general public interested in dermatology, aesthetic trends, skin care, and skin cancer.